Does chronic kidney disease affect the short-term outcomes and prognosis of colorectal cancer surgery? A propensity score matching analysis - Qu, Shu-Pei; Rao, Si-Qi; Hai, Zhan-Xiang; Wang, Chun-Yi (Frontiers in Oncology, 2024)
Purpose The aim of this study was to analyze the effect of chronic kidney disease (CKD) on the short-term outcomes and prognosis of colorectal cancer (CRC) patients who underwent primary surgery. Methods CRC patients who underwent radical surgery were included from Jan 2011 to Jan 2020 in a single hospital. The short-term outcomes and prognosis were compared between the CKD group and the Non-CKD group using propensity score matching (PSM) analysis. Results A total of 4056 patients undergoing CRC surgery were included, including 723 patients in the CKD group and 3333 patients in the Non-CKD group. After 1:1 PSM, there were 666 patients in each group, respectively. No significant difference was found in baseline characteristics between the two groups. (p>0.05). After PSM, the CKD group had a longer postoperative hospital stay (P=0.009) and a higher incidence of overall complications (p=0.050). Cox analysis was performed on matched patients to find predictors of overall survival (OS) and disease-free survival (DFS). We found that age (p<0.01, HR=1.045, 95% CI=1.028–1.062), tumor stage (p<0.01, HR=1.931, 95% CI=1.564–2.385) and overall complications (p<0.01, HR=1.858, 95% CI=1.423–2.425) were independent predictors of OS. Age (p<0.01, HR=1.034, 95% CI=1.020–1.049), tumor stage (p<0.01, HR=1.852, 95% CI=1.537–2.231), and overall complications (p<0.01, HR=1.651, 95% CI=1.295–2.10) were independent predictors of DFS. However, CKD was not an independent predictor of OS or DFS (OS: p=0.619, HR=1.070, 95% CI=0.820–1.396; DFS: p=0.472, HR=1.092, 95% CI=0.859–1.389). Conclusion CKD prolonged postoperative hospital stay; however, CKD might not affect major postoperative complications, OS or DFS of CRC.